HUBUNGAN PANJANG BOBOT, FAKTOR KONDISI DAN STATUS KONSERVASI IKAN KEPALA TIMAH DARI SUNGAI WAY BETUNG KABUPATEN OKU SELATAN - Azmi Afriansyah; Khasanah Cahyani; The Best Akbar Esa Putra (Universitas Sumatera Selatan, 2026)
The blue panchax (Aplocheilus panchax) is a freshwater fish species that inhabits river and swamp waters. This fish is known for its ability to survive under various changes in water quality conditions. This study aimed to explain the length–weight relationship, condition factor, and conservation status of the blue panchax in Way Betung, South OKU Regency. The research method used was direct observation with purposive sampling techniques. Sampling was conducted from April to May 2026. A total of 29 fish samples caught using traditional fishing gear were analyzed at the Kolam Percobaan Laboratory, Aquaculture Study Program, Universitas Sriwijaya. The results showed that the growth pattern of the blue panchax was negatively allometric, with the regression equation W = 2.437L²·⁷⁴ (R² = 0.9645). The condition factor obtained was 1.0068 ± 9.8105, indicating that the fish population in the wild is still in good condition.